DIRECTIVE SPEECH ACTS USED BY SANTRI OF ROUDLOTUT THOLIBIN ISLAMIC BOARDING SCHOOL IN KADEMANGAN KOTA PROBOLINGGO - Arifulloh, Mohammad; Sutrisno, Adi; Mulyono, Sugeng Edy; Aisyah, Rasyidah Nur (JURNAL LITERASI, 2024)
This study analyzes the directive speech used by the students of the Roudlotut Tholibin Probolinggo Islamic Boarding School. This study aims to describe the types of directive speech actions that exist in students of the Roudlotut Tolibin Islamic Boarding School. The scope of this research is a pragmatic field and is carried out in four places, namely Hall, Classroom, Musholla and Canteen. Speech act is a theory that considers that the meaning of linguistic expressions can be explained by following the rules that apply when performing speech acts. The speaker chooses utterances that fit the context. Directive speech is an act of speech that contains the intention of the other person to do something. Among students, there are also many uses for directive speech. Santri is a term for someone who is studying at an Islamic boarding school. The method used is descriptive-qualitative, with data collection techniques through observation and recording and using domain analysis and taxonomy. The data source consists of all Santri conversations. The research was carried out at the Roudlotut Tholibin Islamic boarding school which is located at Jl. KH. Fadhol Kademangan Kademangan Kota Probolinggo. The results of the analysis showed that there were five types of speech actions in students, namely Commanding 66 data, Suggesting 42 data, 35 data, Advice data, and Challenging 12 data. The act of commanding speech is more found because speech occurs between teachers and students.